Technical report: numerical solution of 2-D Maxwell’s Equation using finite difference time domain / Muhd Nur Aliyuddin Abd Samad, Muhammad Faris Ahmad Fadli and Hasan Al Bashri Sarip - Abd Samad, Muhd Nur Aliyuddin; Ahmad Fadhli, Muhammad Faris; Sarip, Hasan Al Bashri (2018)
Maxwell's equations is an equations used describe the relation of electric and magnetic fields. The applications of electric and magnetic field are mostly can be found in daily appliances such as WiFi, mobile phone, microwave, and others. With the increasing of electromagnetic in current technology, Maxwell's equations has become an important equations used to solve the electromagnetic problem. The study on this topic, mostly discuss the basic of Maxwell's equations and how to solve the equations. Because the complexity of the equations, the use of a computer software are required to help in solving the equations. By using a numerical approximation method, the equations become easier to evaluate. From the existing method the method used in this project is a finite difference time domain method or also known as Yee Algorithm to approximate the solutions of Maxwell's equations. In this project, all of the objectives are achieved.